1996
DOI: 10.1093/humrep/11.3.621
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in the developmental rate of in-vitro matured/in-vitro fertilized ovine embryos

Abstract: Sex determination of in-vitro matured/in-vitro fertilized ovine embryos cultured in synthetic oviduct fluid (SOF) medium was performed by the polymerase chain reaction amplification of specific Y DNA sequences so as to test the influence of sex on developmental growth during the preimplantation period. At 144 h post-insemination, embryos with a blastocoel were classified as the fast-developing group, whereas those showing a blastocoel only after this length of time were classified as the slow-developing group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 47 publications
3
26
0
1
Order By: Relevance
“…Embryos produced in vitro in a number of species fall into fast-cleaving and slow-cleaving groups, which are predominantly male and female, respectively. This phenomenon has been observed for bovine (1)(2)(3)(4)(5),** mouse (6,7), sheep (8,9), and human embryos (10). In vivo-produced male pig embryos, both before and subsequent to hatching from the zona pellucida, have also been reported to be larger and to have more cells than female embryos (11,12).…”
mentioning
confidence: 68%
“…Embryos produced in vitro in a number of species fall into fast-cleaving and slow-cleaving groups, which are predominantly male and female, respectively. This phenomenon has been observed for bovine (1)(2)(3)(4)(5),** mouse (6,7), sheep (8,9), and human embryos (10). In vivo-produced male pig embryos, both before and subsequent to hatching from the zona pellucida, have also been reported to be larger and to have more cells than female embryos (11,12).…”
mentioning
confidence: 68%
“…Moreover, anaerobic bacteria are able to colonize the uterine lumen (15,16). Embryos are exceedingly sensitive to oxidative damage (17)(18)(19)(20)(21)(22)(23)(24), and blastocysts produced under low O 2 have significantly more inner cell mass cells than those produced under higher O 2 tensions (25). Accordingly, embryologists generally culture embryos under a low rather than high oxygen atmosphere (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…One possible mechanism for an altered sex ratio is an increased developmental rate in male embryos. Multiple authors have demonstrated increased cellularity and shorter time to blastocoele formation in murine (14)(15)(16), bovine (17)(18)(19), ovine (20), and porcine (21) male embryos compared with female embryos. Proposed mechanisms include metabolic differences (22), Y-linked gene expression (15,23,24), and epigenetic effects (25).…”
mentioning
confidence: 99%